2015
DOI: 10.18632/oncotarget.3333
|View full text |Cite
|
Sign up to set email alerts
|

ROS generation mediates the anti-cancer effects of WZ35 via activating JNK and ER stress apoptotic pathways in gastric cancer

Abstract: Gastric cancer is one of the leading causes of cancer mortality in the world, and finding novel agents and strategies for the treatment of advanced gastric cancer is of urgent need. Curcumin is a well-known natural product with anti-cancer ability, but is limited by its poor chemical stability. In this study, an analog of curcumin with high chemical stability, WZ35, was designed and evaluated for its anti-cancer effects and underlying mechanisms against human gastric cancer. WZ35 showed much stronger anti-prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
114
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(119 citation statements)
references
References 53 publications
5
114
0
Order By: Relevance
“…It has been reported that ROS generation can trigger cells apoptosis through activating both mitochondrial and ER stress pathways [9][10]. This is consistent with the fact that ROS generation can activate of JNK-mitochondrial and ER stress apoptotic pathways [20].…”
Section: Discussionsupporting
confidence: 83%
“…It has been reported that ROS generation can trigger cells apoptosis through activating both mitochondrial and ER stress pathways [9][10]. This is consistent with the fact that ROS generation can activate of JNK-mitochondrial and ER stress apoptotic pathways [20].…”
Section: Discussionsupporting
confidence: 83%
“…Induction of intracellular ROS generation can trigger cell apoptosis via the ER stress pathway29. We previously found that fucoidan induces ROS and ER stress in lung cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, induction of excess ROS in cancer cells via therapeutic approaches, such as chemotherapy and radiotherapy, may trigger ROS-mediated cell death mechanisms39. ROS induce ER stress through modification of proteins and lipids29. Here, we examined effects of fucoidan on ROS-mediated ER stress and apoptosis, developing a potential therapeutic strategy for the treatment of lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Koprowski et al revealed that curcumin could induce growth suppression and apoptosis of cholangiocarcinoma at low treatment concentrations (30). Zou et al reported that an analog of curcumin, WZ35, exhibited the anticancer effect on gastric cancer via activation of the JNK and ER stress apoptotic pathways mediated by ROs generation (31).…”
Section: Discussionmentioning
confidence: 99%